Life in the Diaspora: Christian interpretation of Esther in dialogue with Judaism - Jones, Barry A. (2021)
Christian interpretation of Esther has historically been limited by Christian bias against Judaism and by the teaching of Christian supersessionism. Reconsideration of this history in the aftermath of the Holocaust and in light of the new circumstances of post-Christendom provides an opportunity to reconsider the message of the book for Christian faith and ministry. The article describes how the unique diaspora perspective and theology of Esther provide resources for Christian ethics and discipleship in a post-Christian era.
Keywords: Supersessionism; Purim; Providence; post-Christendom; diaspora theology; Diaspora Judaism; Anti-semitism; Anti-judaism